The main abdominoplasty techniques used in post-bariatric patients after massive weight loss: systematic review - Eurico Arteaga Santiago; Thais Conte Dias Bencini Andrighetti; Matheus Lucena Miranda Meroni; Thays Favaro Fernandes Nolasco; Rodrigo Contente; Carolina Lacerda Souza (Revista Brasileira de Cirurgia Plástica)
Introduction: Obesity is defined by a body mass index (BMI) ≥30 kg/m2, and today approximately 2.1 billion adults are obese. With this high number of obese people, the demand for treatment via bariatric surgery has been increasing to reduce weight, resolve comorbidities and improve quality of life. However, intense weight loss can cause adverse physical, aesthetic, and psychological effects. Plastic surgery becomes essential to resolve these adverse effects. According to the International Society of Plastic Surgery, 112,116 abdominoplasties were performed in 2020, representing 8.6% of all plastic surgeries performed in Brazil. The objective is to present the main abdominoplasty techniques in postbariatric patients. Method: Studies that met the previously defined inclusion criteria were included. Results: A total of 28 references were included in this systematic review. Discussion: Most seek abdominoplasty due to the excess skin remaining in various body regions and the impact on post-bariatric patients’ quality of life and mental health. The surgical techniques addressed are classic abdominoplasty; fleur-de-lis or anchor; circumferences; and Scarpa’s fascia. The total number of complications was 42%; the main ones observed were scarring, skin dehiscence, infection, and necrosis; the three added up to 32%. Conclusion: The improvement in the quality of life of patients undergoing abdominoplasty is evident, but further research is needed to relate abdominoplasty techniques to these patients with postoperative complications.